Giant mature retroperitoneal teratoma in adolescent: a rare case report - Jayaningrum, I. Gusti Ayu Agung Bella Bella; Adiputra, Pande Made Gunawan (International Journal of Research in Medical Sciences, 2021)
Teratomas are neoplasms of the embryonic tissues that typically grow in the gonadal and sacrococcygeal regions of adults and children. Intrabdominal teratomas that occur in adolescent are rare and demand challenging management options. We report a case of an intraabdominal mature cystic teratoma in a 17-year-old female patient. Complete resection of the mass was performed by a laparotomy approach. Radiological imaging is helpful in preoperative diagnosis and planning. Multidisciplinary surgical team planning is also essential to avoid injury to the adjacent organs in duodenal teratoma operation. Complete surgical excision is the treatment of choice, and the prognosis of mature teratomas is excellent.